2018
DOI: 10.1186/s13075-018-1786-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high-intensity interval training on muscle remodeling in rheumatoid arthritis compared to prediabetes

Abstract: BackgroundSarcopenic obesity, associated with greater risk of cardiovascular disease (CVD) and mortality in rheumatoid arthritis (RA), may be related to dysregulated muscle remodeling. To determine whether exercise training could improve remodeling, we measured changes in inter-relationships of plasma galectin-3, skeletal muscle cytokines, and muscle myostatin in patients with RA and prediabetes before and after a high-intensity interval training (HIIT) program.MethodsPreviously sedentary persons with either R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(51 citation statements)
references
References 33 publications
3
47
0
Order By: Relevance
“…RA development, severity, and poor treatment responses are tied to obesity (13). Also, RA is associated with sarcopenia, altered skeletal muscle remodeling, and impaired oxidative metabolism (14, 15). While these metabolic impairments in RA are likely driven in part by epigenetic dysregulation (16), it is unclear whether RA-related miRNAs contribute to the RA comorbidities of obesity and altered metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…RA development, severity, and poor treatment responses are tied to obesity (13). Also, RA is associated with sarcopenia, altered skeletal muscle remodeling, and impaired oxidative metabolism (14, 15). While these metabolic impairments in RA are likely driven in part by epigenetic dysregulation (16), it is unclear whether RA-related miRNAs contribute to the RA comorbidities of obesity and altered metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…For HIIT RA cohort #2, persons with RA (n = 12) completed clinical assessments and underwent skeletal muscle biopsies before and after a 10-week treadmill walking HIIT program (5,17). Similar to the cross-sectional RA cohort #1, all RA participants satis ed the ACR 1987 RA classi cation criteria (19), had no medication changes for 3 months prior to or during the intervention, and were taking less than or equal to prednisone 5 mg per day.…”
Section: Methodsmentioning
confidence: 99%
“…In RA, chronic in ammation is strongly linked to impaired muscle function and "rheumatoid cachexia" or sarcopenic obesity (i.e., decreased muscle mass, increased fat mass, and intramuscular adiposity) (15). Further, the RA skeletal muscle molecular pro le is de ned by altered in ammatory cytokines and impairments in satellite cell function and oxidative metabolism (15)(16)(17)(18). Of particular interest to this study, it is unclear how these RA muscle molecular pathways speci cally 1) contribute to and are affected by in ammation and autoimmunity and 2) in uence and predict immune system changes with exercise training.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] Physical activity and glycemic control may be beneficial in the inhibition of RA progression as well as in the reduction of its prevalence in patients with prediabetes. 24) However, T. Yates study reported that intensive physical intervention or previous physical activity level did not significantly reduce 2-h post prandial or fasting blood glucose levels 25) in adults with prediabetes and the expression of inflammatory markers 14) in patients with either RA or prediabetes. Therefore, the association between the frequency of physical activity and prevalence of RA in adults with prediabetes is unclear.…”
mentioning
confidence: 98%
“…IL-1 inhibitor and IL-10, a natural inhibitor of IL-1β, 11) resulting in decreased disease severity and inflammation in adults with RA, obesity, prediabetes and T2DM. [11][12] Physical activity significantly improved the joint motility, strength and functional ability in patients with either prediabetes or RA via altered pro-inflammatory muscle cytokines [13][14] and reduced the blood glucose levels, further lowering the risk for T2DM. 15) Unfortunately, 71% of adults with RA are unable to maintain normal physical activity, [16][17][18][19] owing to arthritis related barriers to physical activity.…”
mentioning
confidence: 99%